Energy efficiency of PCM integrated in fresh air cooling systems in different climatic conditions. (15th February 2018) - Pop, Octavian G.; Fechete Tutunaru, Lucian; Bode, Florin; Abrudan, Ancuţa C.; Balan, Mugur C.
Highlights: Explicit equations of the PCM apparent heat capacity variation with temperature. Estimation of the required quantity of PCM in thermal energy storage systems. Evaluation of the energy efficiency of PCM in a fresh air cooling system. Specific energy indicators of PCM for feasibility studies are provided. Abstract: The study provides novel and validated explicit equations of the apparent heat capacity variation with temperature for three phase change materials (PCM ): RT20, RT25 and RT27. The developed models of PCM thermal behavior were successfully applied in the energy efficiency analysis of the fresh air cooling system with PCM latent heat storage system, serving a virtual office building considered to be located in different climatic conditions. Following the study, a practical guideline for estimation of the required quantity of PCM in fresh air cooling systems was provided. Two novel specific energy indicators were also proposed, which are useful for feasibility studies. The evaluation of PCM energy efficiency in fresh air cooling systems revealed that savings in the electric energy consumption of (7–41) % can be achieved, depending on the particular local conditions. Limits of the use of PCM in fresh air cooling systems were also provided.